2023
DOI: 10.1002/jhm.13111
|View full text |Cite
|
Sign up to set email alerts
|

Potentially avoidable emergency department use by patients discharged to skilled nursing facilities

Abstract: One‐third of patients discharged from hospitals to skilled nursing facilities (SNF) are sent back to the Emergency Department (ED) within 30 days. Little is known about those patients who are discharged from the ED directly back to SNF. We considered these ED visits as potentially avoidable since they did not result in observation or hospitalization stay. Using a retrospective chart review of 1010 patients with ED visits within 14‐days of discharge to SNF from University of Pennsylvania health system (UPHS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Reasons for ED visits were not captured. However, head injuries, urinary tract infection (UTI), and chest pain were the most frequent diagnoses for SDD ED visits, consistent with other studies 2 . In a multivariable analysis, the authors identified chronic conditions (dementia, congestive heart failure, chronic obstructive pulmonary disease), and facility characteristics (rural SNF setting and those with >70% Medicaid patients) as being associated with an SDD ED visit when compared to patients with no ED visit.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Reasons for ED visits were not captured. However, head injuries, urinary tract infection (UTI), and chest pain were the most frequent diagnoses for SDD ED visits, consistent with other studies 2 . In a multivariable analysis, the authors identified chronic conditions (dementia, congestive heart failure, chronic obstructive pulmonary disease), and facility characteristics (rural SNF setting and those with >70% Medicaid patients) as being associated with an SDD ED visit when compared to patients with no ED visit.…”
supporting
confidence: 79%
“…In their study, Tian et al find that among SNF patients sent to the emergency department (ED), 75% are admitted, while 25% are ED same‐day or next‐day discharges (SDD). They explore the epidemiology of and resource utilization associated with ED SDD, based on the notion that this subset of ED visits may be avoidable 2 . Though the cost of alternatives is not presented and may not be known, in aggregate, these visits cost Medicare an estimated $24.6 million annually.…”
mentioning
confidence: 99%
“…A recent study from a large health system found that 20% of older adults discharged to SNF were sent back to the ED and discharged back to SNF within 2 weeks of SNF admission. 5 ED visits represent a disruption in care and are particularly high-risk for older adults who are vulnerable to adverse events during transitions. However, little is known about the national prevalence and cost of ED visits from SNF that result in same-day discharge back to SNF.…”
Section: Introductionmentioning
confidence: 99%